Diagnostic Efficacy of Ovarian Fluid Cytology in the Identification of Ovarian Tumors in Adolescents and Young Adults (Medical Forum Monthly, 2020)
Objective: To determine the role of cytology in the diagnosis of ovarian tumors in adolescent and young adults.Study Design: Retrospective study.Place and Duration of Study: This study was conducted at the Department of Pathology, Rawal Medical and Dental College, Islamabad from January 2014 to December 2015.Materials and Methods: We retrospectively reviewed 80 cases of females presenting with ovarian masses in adolescent and reproductive age group. At least four slides were prepared for each case by fixing them in 95% ethanol. Hematoxylin and Eosin stain was used to stain cytology smears. Ovarian fluid cytology was compared with histopathological diagnosis keeping histopathology as gold standard.Results: The median age at the time of diagnosis was years (range 11-40 years). Benign tumors occurred in 34 (42.5%) of the patients. Increasing percentage of malignant tumors was seen with the age comprising 42.5%cases above 30 years. There was increased incidence of germ cell tumor in adolescents and young adults comprising 42 (52.5%). Of these cases mature cystic teratoma was the commonest. Epithelial tumors were common in the reproductive age group comprising 46 % of the cases.91% of benign tumors were correctly diagnosed as benign on cytology. Out of 46 (57.5%) malignant cases, 80% were correctly diagnosed as malignant on cytology. Overall sensitivity and Specificity of ovarian fluid cytology was 80.4% and 94% respectively.Conclusion: Cytology is a simple, rapid and economical diagnostic tool with high accuracy rate and can be utilized to differentiate between histological subtypes and nature of the tumor in adjunct with histopathology for suitable treatment regimens in adolescents and young adults.